From dirty to delicacy? Changing exploitation in China threatens the world's largest amphibians. Issue 2 (21st February 2021) - Turvey, Samuel T.; Chen, Shu; Tapley, Benjamin; Liang, Zhiqiang; Wei, Gang; Yang, Jian; Wang, Jie; Wu, Minyao; Redbond, Jay; Brown, Thomas; Cunningham, Andrew A.
Abstract: Determining the dynamics and sustainability of human interactions with threatened species is essential to inform evidence‐based conservation, but data can be challenging to collect across large areas and multiple user groups. Chinese giant salamanders Andrias spp. are critically depleted across China. Wild populations were exploited during the 20th century, and more recently to support a large‐scale farming industry. However, robust data remain largely unavailable on the timing of population declines in relation to changing human pressures, on primary drivers of exploitation, or on the effectiveness of conservation legislation. We conducted a series of large‐scale interview surveys across the range of giant salamanders in China, targeting potential rural and urban user groups, and stakeholders involved with giant salamander exploitation and policy management (comprising 2, 932 rural households, 66 salamander farms, 115 county government officials and 835 urban consumers). Giant salamander populations were probably declining from at least the 1980s due to exploitation for food, and negative cultural values associated with these animals have not prevented rural consumption. There has been a major escalation in exploitation following the establishment of a large‐scale giant salamander farming industry in the 2000s. Our results demonstrate wide‐scale and largely unregulated illegal hunting to stock farms at a country‐wide scale in order to support demand by urban consumers for high‐prestige rare meat. We estimate there were at least 42, 000 wild‐caught breeding adult giant salamanders and 164, 000 wild‐caught subadults in farms across China at the time of our survey. Salamander farming probably poses unsustainable pressure on giant salamander populations. Existing legislation has clearly proved ineffective at preventing the stocking of farms with wild‐caught animals, and our findings highlight an important gap in the effectiveness of China's conservation protection for some of its highest‐priority threatened species. Tackling this problem will likely require multiple coordinated approaches, including enforcement of legislation, increased penalties for removing giant salamanders from the wild, permanent identification of captive‐bred giant salamanders, and consumer‐focused interventions to reduce urban demand. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.